Cell surface vimentin-targeted monoclonal antibody 86C increases sensitivity to temozolomide in glioma stem cells. (1st October 2018) - Noh, Hyangsoon; Zhao, Qingnan; Yan, Jun; Kong, Ling-Yuan; Gabrusiewicz, Konrad; Hong, Sungguan; Xia, Xueqing; Heimberger, Amy B.; Li, Shulin
Abstract: Glioblastoma multiforme (GBM) is the most prevalent and aggressive brain tumor. The current standard therapy, which includes radiation and chemotherapy, is frequently ineffective partially because of drug resistance and poor penetration of the blood-brain barrier. Reducing resistance and increasing sensitivity to chemotherapy may improve outcomes. Glioma stem cells (GSCs) are a source of relapse and chemoresistance in GBM; sensitization of GSCs to temozoliomide (TMZ), the primary chemotherapeutic agent used to treat GBM, is therefore integral for therapeutic efficacy. We previously discovered a unique tumor-specific target, cell surface vimentin (CSV), on patient-derived GSCs. In this study, we found that the anti-CSV monoclonal antibody 86C efficiently increased GSC sensitivity to TMZ. The combination TMZ+86C induced significantly greater antitumor effects than TMZ alone in eight of 12 GSC lines. TMZ+86C–sensitive GSCs had higher CSV expression overall and faster CSV resurfacing among CSV − GSCs compared with TMZ+86C–resistant GSCs. Finally, TMZ+86C increased apoptosis of tumor cells and prolonged survival compared with either drug alone in GBM mouse models. The combination of TMZ+86C represents a promising strategy to reverse GSC chemoresistance. Highlights: Anti-CSV monoclonal antibody 86C sensitize GSCs to TMZ treatment. GSCs with higher CSV expression are more sensitive to TMZ+86C. GSCs with higher CSV resurfacing rate among CSV − cells are more sensitive to TMZ+86C. TMZ+86C increased apoptosis and prolonged survival in GBM models. Tumor-specific CSV antibody 86C can efficiently target human GSCs to increase their sensitivity to TMZ.